La position des pays de l’ALBA et de l’UNASUR face à la guerre en Libye - Hortense Faivre d'Arcier-Flores (L’Année du Maghreb)
To better understand the Bolivarian countries’ condemnation of the NATO military intervention in Libya and their support of the legitimacy of the Guide of the Revolution Muammar Gaddafi, we had to examine the Latin American context, since the emergence of the Cuban Revolution to the establishment of a new regional geopolitical balance. Beyond the factual aspect, the purpose of this article is to identify, through the political discourse of Latin American leaders, the ideological filiations that have persisted since the 1960s in the founding principles and joint statements of existing regional organizations among which the Bolivarian Alliance for the Peoples of Our America (ALBA) is the most politically assertive.